Data-at-rest Encryption for the IBM Spectrum Accelerate family - Dufrasne, Bertrand; Fridli, Roman; Greenfield, Andrew (IBM redpaper, 2019)
With the ever-growing landscape of national, state, and local regulations, industry requirements, and increased security threats, ensuring the protection of an organization's information is a key part of operating a successful business. Encrypting data-at-rest is a key element when addressing these concerns. Most storage products offer encryption at an additional cost. The IBM® Spectrum Accelerate family, which includes IBM XIV® Storage System, IBM FlashSystem® A9000, IBM FlashSystem A9000R system(s), and IBM Spectrum"!Accelerate Software provides data-at-rest encryption at no charge. Clients can take advantage of encryption and still benefit from the lower total cost of ownership (TCO) that the IBM Spectrum Accelerate"!family offers. For IBM FlashSystem A9000 and A9000R, clients now have a choice between an external key manager-based implementation or a local key based encryption implementation. The local key solution offers a simplified deployment of data-at-rest encryption. This IBM Redpaper"!publication explains the architecture and design of the XIV and IBM FlashSystem A9000 and A9000R encryption solutions. Details are provided for configuring and implementing both solutions